2019
DOI: 10.5222/head.2019.139
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Bariatric Surgery and Nursing Care

Abstract: Obezite prevelansı epidemik oranlarda artış göstermekte; obezite ve ona eşlik eden komorbid durumları majör halk sağlığı sorunu haline getirmektedir. Bununla birlikte obezite için diyet, fiziksel aktivitenin arttırılması, davranış değişikliği tedavisi ve farmakoterapi gibi birkaç etkili tedavi yöntemi bulunmakta ancak bu yöntemler sadece geçici kilo kaybı sağlamaktadır. Midenin boyutunu kısıtlayan ve kalori alımını sınırlayan bariatrik cerrahi, uzun dönemde kilo kaybı sağlamada ve obeziteye eşlik eden komorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Bypassing a part of the gastric mucosa in bariatric surgery may lead to iron and B12 deficiency, and bypassing the duodenum and proximal jejunum may lead to impaired absorption of calcium and vitamin D from the intestines. [20][21][22] Bariatric surgery has also been reported to lead to decreased absorption of nutrients such as vitamins A, K, iron, selenium, zinc and copper. 23,24 The incidence of vitamin C deficiency in bariatric patients is 10-50%, calcium deficiency occurs in 10-25% at the end of the second year after surgery, 25-48% at the end of the fourth year, and vitamin D deficiency occurs in 17-52% and 50-63% of patients during the same period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bypassing a part of the gastric mucosa in bariatric surgery may lead to iron and B12 deficiency, and bypassing the duodenum and proximal jejunum may lead to impaired absorption of calcium and vitamin D from the intestines. [20][21][22] Bariatric surgery has also been reported to lead to decreased absorption of nutrients such as vitamins A, K, iron, selenium, zinc and copper. 23,24 The incidence of vitamin C deficiency in bariatric patients is 10-50%, calcium deficiency occurs in 10-25% at the end of the second year after surgery, 25-48% at the end of the fourth year, and vitamin D deficiency occurs in 17-52% and 50-63% of patients during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…This situation may cause an increase in hair loss. 20,29 According to the meta-analysis conducted by Zhang et al 30 , the incidence of hair loss in bariatric patients was reported to be 57%. Research results in the literature were similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that successful outcomes have been obtained from sleeve gastrectomy surgeries (Hendricks et al, 2016; Hoyuela, 2017). However, as in other surgeries, it is possible to encounter problems in bariatric surgery in the early stages (Güven, 2019; Lim et al, 2018). In the postoperative period, respiratory problems such as pneumonia and atelectasis are common in obese patients (Güven, 2019; Sümer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, as in other surgeries, it is possible to encounter problems in bariatric surgery in the early stages (Güven, 2019; Lim et al, 2018). In the postoperative period, respiratory problems such as pneumonia and atelectasis are common in obese patients (Güven, 2019; Sümer et al, 2020). Also, patients experience postoperative nausea/vomiting and pain.…”
Section: Introductionmentioning
confidence: 99%